Polypyridyl CoII-Curcumin Complexes as Photoactivated Anticancer and Antibacterial Agents - Yadav A.K.; Singh V.; Kushwaha R.; Dolui D.; Rai R.; Dhar P.; Dutta A.; Koch B.; Banerjee S. (My University, 2025)
Four new CoII complexes, [Co(bpy)2(acac)]Cl (1), [Co(phen)2(acac)]Cl (2), [Co(bpy)2(cur)]Cl (3), [Co(phen)2(cur)]Cl (4), where bpy=2,2’-bipyridine (1 and 3), phen=1,10-phenanthroline (2 and 4), acac=acetylacetonate (1 and 2), cur=curcumin monoanion (3 and 4) have been designed, synthesized and fully characterized. The X-ray crystal structures of 1 and 2 indicated that the CoN4O2 core has a distorted octahedral geometry. The photoactivity of these complexes was tuned by varying the π conjugation in the ligands. Curcumin complexes 3 and 4 had an intense absorption band near 435 nm, which made them useful as visible-light photodynamic therapy agents; they also showed fluorescence with λem≈565 nm. This fluorescence was useful for studying their intracellular uptake and localization in MCF-7 breast cancer cells. The acetylacetonate complexes (1 and 2) were used as control complexes to understand the role of curcumin. The white-light-triggered anticancer profiles of the cytosol targeting complexes 3 and 4 were investigated in detail. These non-dark toxic complexes displayed significant apoptotic photo-cytotoxicity (under visible light) against MCF-7 cells through ROS generation. The control complexes 1 and 2 did not induce significant cell death in the light or dark. Interestingly, 1-4 produced a remarkable antibacterial response upon light exposure. Overall, the reported results here can increase the boundary of the CoII-based anticancer and antibacterial drug development. © 2023 Wiley-VCH GmbH.